POTENSI PREBIOTIK NASI UNGU - Agustina Souripet (AGRITEKNO: Jurnal Teknologi Pertanian, 2016)
The aim of this research is to analyze the preference level and prebiotic potency of purple rice that is preffered by group of people in Bali. Purple rice with various pasta proportions, which are 100, 200, 300, 400 and 500 g added to 700 g of rice and tested of preference level. The next part was analyzing the Organoleptic and prebiotic capacity of the best purple rice were tested. Prebiotic capacity testing using Bifidobacterium longum and Lactobacillus acidophillus cultured in MRS modified media plus coarse fibers of purple rice and used control of fibers of fresh sweet potato, sweet potato pasta, rice and cooked rice. Parameters observed were preferable level of purple rice, probiotic bacteria growth and prebiotic activity score. This research were designed as Completely Randomized Design (RAL) with 2 replicates and data of the results were analyze at variation of 95% reliance interval and, if there was real difference, it would be continued by Duncan’s Multiple Range Test. The results of research indicated that purple rice made of ratio of 100 g rice: 300 g mixture was preferably by panelists. Prebiotic activity score of purple rice was higher than white rice, -0.006 + 0.2 for Bifidobacterium longum and -0.015 + 05 for Lactobacillus acidophilus were means that purple rice has best capacity to become a prebiotic than cooked rice or white rice.